The Impact of the E-Service Quality (E-SQ) of Online Databases on Users' Behavioural Intentions: A Perspective of Postgraduate Students - Dia Zeglat; Fayiz Shrafat; Ziad Al-Smadi (International Review of Management and Marketing, 2016)
This study aimed to explore the impact of the e-service quality (E-SQ) of the online academic databases offered in the Jordanian academic institutions on end users' behavioural intentions. To do that, the current study employed a quantitative survey approach to test a set of hypotheses and answer the research questions. This study implemented the convenience sampling technique to select a representative sample of postgraduate students at Jordanian public and private universities. Two hundred and eighty (280) questionnaires were distributed, 230 questionnaires were completed, and 50 questionnaires were excluded. The findings of the study showed that only four dimensions of E-SQ (ease of use, website design, security, and reliability variables) have a positive impact on users' satisfaction. The results also showed that five dimensions of E-SQ (ease of use, security, reliability, website design, and responsiveness) have a positive impact on users' behavioural intentions. Furthermore, the results demonstrated that users' satisfaction has a positive impact on users' behavioural intentions. The study also concluded that user satisfaction has mediated partially the impact of E-SQ on behavioural intention in the online database setting.